Test fairness of the in-house College English examination for Chinese non-English major undergraduates: a case study - Li, Kangxi; Kong, Mengting; Li, Liye; Lu, Jingwen (Frontiers in Education, 2025)
IntroductionThe in-house College English examination is a high-stakes assessment for College English, a compulsory course for most non-English major undergraduates in China. However, the fairness of such examinations has not received due attention.MethodsThis paper employs Kunnan’s Test Fairness Framework to investigate common issues of test fairness related to the in-house College English examination, using a university in East China as an example. The data analyzed include the College English examination results of 5,680 non-English major undergraduates from 2018 to 2020.ResultThe research finds various fairness problems in terms of validity, absence of bias, access, administration, and social consequences. These issues can be attributed to underlying factors such as lack of language assessment literacy, time, and funding on the part of examiners or administrators.DiscussionHence, this research proposes a holistic approach to improve test fairness, involving all stakeholders and all procedures in the in-house College English examination. Collaborating with external experts on language tests and lowering the stakes of in-house examinations are suggested as effective measures to mitigate test unfairness issues.